A Review of Marine Bacterial Intracellular and Extracellular Bioactive Compounds as Novel Antibacterial and Anti-Inflammation Agents - Karim, Harningsih; Azis, Arief; Ramadani, Ananda; Anita, Anita; Ahmad, Ahyar; Natsir, Hasnah; Taba, Paulina; Putri, Suriati Eka; Sarlan, Sarlan; Larekeng, Siti Halimah; Irfandi, Rizal (Universitas Gadjah Mada, 2025)
Unique and varied bioactive compounds produced by the ocean have drawn attention and served as a focus for creating antibacterial and anti-inflammatory agents. As part of the approach for locating these research sources, databases such as PubMed, Science Direct, MDPI, Google Scholar, Springer Link, Web of Science, Scopus, and Wiley Online Library were used to identify completed studies. Numerous intriguing bioactive compounds have so far been isolated from marine bacteria. A crucial resource in the ongoing search for novel peptides, proteins, lipids, nucleosides, enzymes, alkaloids, polyketides, and terpenoids is the diversity of marine bacterium strains. This review summarizes several bacterial intracellular and extracellular bioactive compounds that have been applied as antibacterial and anti-inflammatory agents in 2016–2024, which we present in the form of structures, species sources, and evaluations of these compounds' antibacterial and anti-inflammatory activities. Therefore, this review article can be used as a recommendation for utilizing biomaterials from marine bacteria that are promising in the future for industrial-scale production of antibacterial and anti-inflammatory agents.